Heat transfer in boundary layer regions of non-Newtonian nanofluid flows - Gunathilaka, W. A. N. A.; Karunathilake, N. G. A. (Faculty of Science, University of Kelaniya Sri Lanka, 2024)
Heat and mass transfer in Nanofluids exhibit unique properties, and therefore they are used in many industrial applications, specifically in fuel cells, hybrid power trains, vehicle thermal management, domestic refrigerators, chillers, heat exchangers, and grinding machinery. In many of these applications, thin boundary layers are formed, and hence the impact of the flow parameters in these regions are crucial to maintain the quality of industrial products. In this research work, we improve a mathematical model of the boundary layer formation in non-Newtonian nanofluids. The analysis begins with the governing equations of the fluid flow derived from the conservation of mass, momentum, energy, and nanoparticle volume fraction. The modified second-grade fluid model is employed as the rheological model to close the system. The governing set of partial differential equations has been converted into nonlinear ordinary differential equations using similarity transformations. The resulting nonlinear coupled system of ordinary differential equations has been solved numerically by using the shooting method. The qualitative impact of Lewis number, Brownian motion parameter, magnetic parameter, local thermal Grashof parameter, local solutal Grashof parameter, power law index, and the porous parameter on the radial and axial fluid velocities, temperature, and nanoparticle volume fraction profiles in the boundary layers have been investigated. The results have been simulated and presented graphically for comparison. Our observations indicate that the axial velocity decreases with increasing Lewis number and Brownian motion parameter, but it increases with increasing local solutal Grashof parameter and power law index. The axial velocity demonstrates mixed behaviour in different flow regions with the magnetic parameter, porous parameter, and local thermal Grashof parameter. The radial velocity decreases with increasing Lewis number and Brownian motion parameter, but it increases with increasing power law index. The radial velocity demonstrates mixed behaviour in different flow regions with the porous parameter, magnetic parameter, local solutal Grashof parameter, and local thermal Grashof parameter. The temperature decreases with increasing local solutal Grashof parameter and power law index, but it increases with increasing Lewis number, Brownian motion parameter, local thermal Grashof parameter, magnetic parameter, and porous parameter. The nanoparticle volume fraction decreases with increasing Lewis number, Brownian motion parameter, power law index, and local solutal Grashof parameter, but it increases with increasing local thermal Grashof parameter, magnetic parameter, and porous parameter.
Keywords: Boundary layer, Modified second-grade fluid, Nanofluids, Nanoparticles, Similarity transformations